Implementation of Public Sector Entrepreneurship Using The Bmc Model in Military Cooperative Services - Avianti, Widiya; Rukayat, Yayat; Permatasari, Arini; Listiya, Alika; Violeta, Arlienda (Bulletin of Management and Business, 2025)
This research discusses the concept of public sector entrepreneurship by implementing a business model canvas to assist the implementation of cooperative work programs, including those under the auspices of the military, to describe, analyze, and develop their business models. Business Model Canvas (BMC) is a useful tool for articulating and managing all the key elements in a cooperative business, descriptive qualitative research method, in accordance with research in the field of social society by conducting an analytical study contained in SWOT analysis so that it can be known the strengths, weaknesses, opportunities and threats of this public service business to be able to develop cooperative service planning that can provide maximum service to its members as well as become a community service partner.